A bibliometric analysis of research on the translation of advertising. An inconstant object of study? - Franco Aixelá, Javier (Meta, 2023)
The first studies detected on the translation of advertising date back to a special issue published by the journal Meta (Vinay 1957), after which there was complete silence until 1968 and then barely twenty articles until 1990. This score of articles in 33 years then abruptly gives way to an exponential growth with hundreds around the turn of the century… and then slows down to the hundred detected so far for the second decade of the new millennium. The sudden great interest in the translation of advertising has suffered a surprising decline in comparison with the sustained growth of TS (Translation Studies) in general. From the point of view of TS, it would be reasonable to assume that advertising would be especially interesting because there is an application of an enhanced creative translation mode due to the frequent need to localise or transcreate in order to influence the potential consumers in their new context. In this contribution, we will try to analyse, using a bibliometric perspective (see De Bellis 2009), the almost 500 publications on the translation of advertising found so far. Using quantitatively-based methodology and qualitative contextualisation, and taking as our main source the BITRA database (more than 86,000 entries on TS as of November 2021), we will describe and analyse key bibliometric parameters such as the evolution, productivity, authorship patterns, language distribution, thematic concurrence, impact and accessibility of the academic production in the field.